Coronavirus in human diseases: Mechanisms and advances in clinical treatment. Issue 3 (1st October 2020) - Lin, Panpan; Wang, Manni; Wei, Yuquan; Kim, Taewan; Wei, Xiawei
Abstract: Coronaviruses (CoVs), a subfamily of coronavirinae, are a panel of single‐stranded RNA virus. Human coronavirus (HCoV) strains (HCoV‐229E, HCoV‐OC43, HCoV‐HKU1, HCoV‐NL63) usually cause mild upper respiratory diseases and are believed to be harmless. However, other HCoVs, associated with severe acute respiratory syndrome, Middle East respiratory syndrome, and COVID‐19, have been identified as important pathogens due to their potent infectivity and lethality worldwide. Moreover, currently, no effective antiviral drugs treatments are available so far. In this review, we summarize the biological characters of HCoVs, their association with human diseases, and current therapeutic options for the three severe HCoVs. We also highlight the discussion about novel treatment strategies for HCoVs infections. Abstract : Current mechanisms of anti‐CoV therapeutic strategies. The idea to disturb the normal life cycle of the virus provides significant insights into the clinical treatment strategies. All of SARS‐CoV, MERS‐CoV, and SARS‐CoV‐2 encode structure proteins (like S protein), nonstructure proteins (eg, PLpro, 3CLpro, RdRp, and helicase), and accessory proteins that are essential for the viral life cycle and that are considered as important targets for the development of antiviral agents. Additionally, enhancement of INF response and several other cell signaling pathways are also regarded as potential anti‐CoV strategies.